Hubungan Disiplin Kerja dengan Kinerja Karyawan BPJS Ketenagakerjaan Bogor Kota - Khoirunnisa, Khoirunnisa; Atika, Dewi; Rully, Tutus (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: The BPJS Ketenagakerjaan Bogor City probe is a response to employee performance difficulties caused by less-than-ideal work discipline. Here, we are interested in the strength of the relationship between work discipline (X) and employee performance (Y), one of the dependent variables. Specifically, this study tests its assumptions using the explanatory survey research method. Methods: . A combination of qualitative and quantitative data is present in this researcher's dataset. We use primary and secondary sources to compile our data. The sample consists of 319 comments and responses from BPJS Ketenagakerjaan Bogor City employees. Many types of analyses are used, including descriptive analysis, quantitative analysis, determination coefficient, and Pearson product-moment correlation coefficient. Data is processed using IBM's SPSS 25 software. Results: . The results showed that at BPJS Ketenagakerjaan Bogor City, there is a substantial correlation between workers' work discipline and their performance (r=0.946). Employee performance is positively connected with work discipline at BPJS Ketenagakerjaan Bogor City. Keywords: Work discipline, employee performance.